Delay effect of Yellow River discharge on the water exchange through the Bohai Strait - Wu, Danning; Yu, Xiaojie; Guo, Xinyu; Wang, Yucheng; Gao, Huiwang; Zou, Tao; Tang, Jianhui (Frontiers in Marine Science, 2025)
The exchange of water through the Bohai Strait, located between the Bohai Sea and the Yellow Sea, plays a crucial role in controlling physical-biogeochemical conditions in the coastal seas off northern and eastern China. We investigated the characteristics of the water exchange through the strait using a numerical model. Our results showed that the residual current was featured with inflow in the northern part and outflow in the southern part of the strait, consistent with previous studies. A two-layer structure, i.e. outflow in the surface layer and inflow in the bottom layer, was newly found in the southern part of the strait. Through a series of numerical experiments, we found that the two-layer structure was induced by density-driven currents and was strongest in summer. Furthermore, the seasonal variation of net water flux through the strait showed correspondence to that of the Yellow River discharge. We investigated the effect of Yellow River discharge on the water exchange through Bohai Strait by additional experiments. Results showed that the response of net water flux through the strait was nearly synchronous with the variation in the Yellow River discharge; however, the response of inflow/outflow flux was a combination of synchronous and delayed responses to the Yellow River discharge. Compared with the maximum Yellow River discharge in July, the largest increase in outflow volume through the strait occurred in next March. The synchronous response is induced by the barotropic effect, while the asynchronous response is due to the baroclinic effect of the Yellow River discharge. Meanwhile, tracers released from the Yellow River mouth at the end of June were detected at the southern strait in next January. Therefore, the Yellow River discharge likely has a delay effect on the Bohai Strait water exchange with an approximate lag of 7–9 months.